Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/pharmaceutics11100499
|View full text |Cite
|
Sign up to set email alerts
|

Preformulation Study of Electrospun Haemanthamine-Loaded Amphiphilic Nanofibers Intended for a Solid Template for Self-Assembled Liposomes

Abstract: Haemanthamine (HAE) has been proven as a potential anticancer agent. However, the therapeutic use of this plant-origin alkaloid to date is limited due to the chemical instability and poorly water-soluble characteristics of the agent. To overcome these challenges, we developed novel amphiphilic electrospun nanofibers (NFs) loaded with HAE, phosphatidylcholine (PC) and polyvinylpyrrolidone (PVP), and intended for a stabilizing platform (template) of self-assembled liposomes of the active agent. The NFs were fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…The thermal behavior of active pharmaceutical ingredients (APIs) as pure components in binary mixtures with excipients and in pharmaceutical formulations is of great importance in drug science [21][22][23][24][25][26]. Even if in the case of pharmaceuticals, the term "stability" is usually correlated with the loss of the active pharmaceutical ingredient from formulation, and "solid-state stability" can also designate the response of an API or a pharmaceutical formulation to thermal stress.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal behavior of active pharmaceutical ingredients (APIs) as pure components in binary mixtures with excipients and in pharmaceutical formulations is of great importance in drug science [21][22][23][24][25][26]. Even if in the case of pharmaceuticals, the term "stability" is usually correlated with the loss of the active pharmaceutical ingredient from formulation, and "solid-state stability" can also designate the response of an API or a pharmaceutical formulation to thermal stress.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 8 has been proven to have a cytotoxic activity, but it is very poorly soluble in water. Therefore, we recently developed novel haemanthamine (compound 8)-loaded amphiphilic nanofibers to overcome these formulation challenges 26 . Noticeably, secondary metabolites from natural products have been the most successful leads in the discovery and development of www.nature.com/scientificreports/ novel drugs 27,28 .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the development of novel drug delivery systems for natural compounds could resolve these critical issues, thus leading to novel and versatile applications of natural products in medicine. In our recent study, we succeeded to yield (through extraction and crystallization) haemanthamine (compound 8) in the amounts enough to fabricate the active-loaded amphiphilic nanofibers 26 . The results suggested that the formulation of such amphiphilic nanofibers for haemanthamine could provide a promising drug delivery system for the present large-molecule and poorly water-soluble active agent.…”
Section: Resultsmentioning
confidence: 99%
“…Ideal drug delivery systems have been developed to achieve the best therapeutic effects and lowest toxicity problems [ 1 ]. The rapid progress in the field of nanotechnology has led to the development of many techniques for the production of numerous nano-scale composites [ 2 , 3 ], of which nanofibers have received considerable attention [ 4 ] due to diversity in the fabrication technologies and applications [ 5 , 6 ], especially in the fields of pharmaceutical drug delivery [ 7 , 8 , 9 ], biomedical applications including wound dressing [ 10 , 11 , 12 , 13 ], and tissue engineering [ 14 , 15 ]. Electrospinning (ES) has been considered one of the most efficient techniques used for the synthesis of nanomaterials since the 20th century [ 16 ], and great works have been done in the late 1990s and early part of the 21st century [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%